2011
DOI: 10.1111/j.1469-8137.2011.03833.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expression dominance in the natural allopolyploid Coffea arabica is massively affected by growth temperature

Abstract: Summary• Polyploidy occurs throughout the evolutionary history of many plants and considerably impacts species diversity, giving rise to novel phenotypes and leading to ecological diversification and colonization of new niches. Recent studies have documented dynamic changes in plant polyploid gene expression, which reflect the genomic and functional plasticity of duplicate genes and genomes.• The aim of the present study was to describe genomic expression dominance between a relatively recently formed natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 42 publications
8
88
0
1
Order By: Relevance
“…Most reviews of allopolyploid gene expression in the last 10 years have emphasized novel and variable patterns of gene expression [96][97][98][99][100][101][102], due to multiple recent discoveries of alteration of gene expression patterns [23,26,45,46,103] and variation among tissues and progenies of similar allopolyploids [50,104]. In this review, we have concentrated on the converse: continuity among allopolyploids and their diploid progenitors, inspired by the early insights of Leslie Gottlieb in this field.…”
Section: Resultsmentioning
confidence: 99%
“…Most reviews of allopolyploid gene expression in the last 10 years have emphasized novel and variable patterns of gene expression [96][97][98][99][100][101][102], due to multiple recent discoveries of alteration of gene expression patterns [23,26,45,46,103] and variation among tissues and progenies of similar allopolyploids [50,104]. In this review, we have concentrated on the converse: continuity among allopolyploids and their diploid progenitors, inspired by the early insights of Leslie Gottlieb in this field.…”
Section: Resultsmentioning
confidence: 99%
“…The advent and subsequent widespread use of microarray and next-generation sequencing technologies have led to a rapid increase in exploration of gene expression at the transcriptional level (Adams et al 2003;Hegarty et al 2005;Bottley et al 2006;Wang et al 2006;Gaeta et al 2007;Flagel et al 2008;Hovav et al 2008;Chaudhary et al 2009;Rapp et al 2009;Buggs et al 2010a;Buggs et al 2010b;Chague et al 2010;Chelaifa et al 2010;Flagel and Wendel 2010;Koh et al 2010;Bardil et al 2011;Chelaifa et al 2013;Yoo et al 2013). However, the transcriptome itself is insufficient for understanding the end products of gene expression and phenotypic outcomes (Rose et al 2004;Thelen and Peck 2007;Karr 2008;Vogel and Marcotte 2012;Ponnala et al 2014).…”
mentioning
confidence: 99%
“…Many of these insights have been corroborated in other systems: expression-level dominance has been found in Coffea arabica (Bardil et al, 2011) and Spartina anglica (Chelaifa et al, 2010) and homeologous expression bias has been found in most allopolyploids where it has been studied (for example, Wang et al, 2006;Buggs et al, 2011;Schnable et al, 2011). Whilst many questions remain to be answered about the contribution of allopolyploidy to plant productivity (Soltis et al, 2010), it seems likely that homeologous expression bias and genome level dominance have an important role.…”
mentioning
confidence: 60%